Facile preparation of urchin-like ZnO nanostructures and their photocatalytic performance. Issue 10 (1st August 2016) - Yang, Jun; Jia, Hanxiang; Lv, Xiangzhou; Wang, Yongqian
Abstract: Urchin-like hierarchical ZnO nanostructures consisting of cone-shaped nanorods have been successfully obtained by electrodeposition-hydrothermal method. The as prepared samples were characterized by FESEM, XRD, UV–vis, PL and photocatalytic test. We have studied the important influence of hydrothermal time on the structural, morphological and optical properties. In the FESEM images, the cone-shaped ZnO nanorods radiate from the center of the nanostructures forming a spherical urchin-like shape with a diameter of 5–10 µm. The average diameter and the length of the cone-shaped ZnO nanorods can be identified as 0.1–1 µm and 3–5 µm, respectively. In the PL spectra, a violet emission band at about 402 nm and two blue emission bands at about 446 nm and 465 nm can be observed at room temperature. In comparison with the others, urchin-like ZnO nanostructures prepared under 4 h showed enhanced photocatalytic performance. The enhanced photocatalytic activity of urchin-like ZnO nanostructures might be resulting from the higher concentration of surface oxygen vacancies.